Effects of strength training on muscle fibre types and size: consequences for athletes training for high-intensity sport - Andersen, J. L.; Aagaard, P. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Training toward improving performance in sports involving high intense exercise can and is done in many different ways based on a mixture of tradition in the specific sport, coaches' experience and scientific recommendations. Strength training is a form of training that now-a-days have found its way into almost all sports in which high intense work is conducted. In this review we will focus on a few selected aspects and consequences of strength training; namely what effects do strength training have of muscle fiber type composition, and how may these effects change the contractile properties of the muscle and finally how will this affect the performance of the athlete. In addition, the review will deal with muscle hypertrophy and how it develops with strength training. Overall, it is not the purpose of this review to give a comprehensive up-date of the area, but to pin-point a few issues from which functional training advises can be made. Thus, more than a review in the traditional context this review should be viewed upon as an attempt to bring sports-physiologists and coaches or others working directly with the athletes together for a mutual discussion on how recently acquired physiological knowledge are put into practise.